A rare case of methimazole-induced cholestatic jaundice in an elderly man of Asian ethnicity with hyperthyroidism: A case report. Issue 49 (December 2017) - Ji, Hongjian; Yue, Feng; Song, Jianxiang; Zhou, Xiaohua
Abstract: Background: Methimazole is an antithyroid drug that is widely used for the treatment of hyperthyroidism. As an inhibitor of the enzyme thyroperoxidase, methimazole is generally well-tolerated. However, there have been increasing reports of methimazole-induced liver damage, although this effect of methimazole has been limited by the absence of objective diagnosis of the liver condition or the inappropriate use of the Naranjo scale. We present the case of an elderly man with hyperthyroidism, gastritis, and epilepsy who developed liver damage after administration of multiple drugs. Key points from the case: Considering the low sensitivity of the Naranjo scale in detecting rare reactions associated with liver damage, we used the Roussel-Uclaf Causality Assessment Method scale, with a finding of cholestatic jaundice hepatitis induced by methimazole. The patient's liver enzyme levels improved after discontinuation of methimazole. Main lessons learned: Our case underlines the possible hepatoxicity associated with the use of methimazole. A review of the literature confirmed a selective hepatoxicity risk in individuals of Asian ethnicity, which has not been identified in Caucasian or Black populations. Physicians should be aware of the risk of hepatoxicity when prescribing oral methimazole to patients of Asian ethnicity.